2017
DOI: 10.1002/2016jg003716
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Terrestrial Ecosystem Model Parameters Using Atmospheric CO2 Concentration Data With the Global Carbon Assimilation System (GCAS)

Abstract: The Global Carbon Assimilation System that assimilates ground‐based atmospheric CO2 data is used to estimate several key parameters in a terrestrial ecosystem model for the purpose of improving carbon cycle simulation. The optimized parameters are the leaf maximum carboxylation rate at 25°C ( Vmax25), the temperature sensitivity of ecosystem respiration (Q10), and the soil carbon pool size. The optimization is performed at the global scale at 1° resolution for the period from 2002 to 2008. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Its rainfall estimates are provided at relatively high spatial resolution (0.25° × 0.25°) and 3-hourly time stapes, in both real and postreal time to meet a wide range of research needs. The latest version of TMPA_3B42v7 rainfall product was released in June 2012, and recent studies indicated that 3B42v7 estimates improve upon 3B42v6 (Bigiarini et al 2017;Chen et al 2013). Nowadays, after more than 17 years of data collection, the instruments turned off on April 8, 2015, after the spacecraft exhausted its fuel reserves and replaced by Global Precipitation Measurement (GPM) mission.…”
Section: Chirps-2 and Tmpa-3b42v7mentioning
confidence: 99%
“…Its rainfall estimates are provided at relatively high spatial resolution (0.25° × 0.25°) and 3-hourly time stapes, in both real and postreal time to meet a wide range of research needs. The latest version of TMPA_3B42v7 rainfall product was released in June 2012, and recent studies indicated that 3B42v7 estimates improve upon 3B42v6 (Bigiarini et al 2017;Chen et al 2013). Nowadays, after more than 17 years of data collection, the instruments turned off on April 8, 2015, after the spacecraft exhausted its fuel reserves and replaced by Global Precipitation Measurement (GPM) mission.…”
Section: Chirps-2 and Tmpa-3b42v7mentioning
confidence: 99%
“…BEPS is in development for the last years [53]. Although BEPS was initially developed for boreal ecosystems, it was expanded and used for temperate and tropical ecosystems in regional and global scales [48,51,52,[54][55][56][57][58][59] and for the estimation of winter wheat yield in China [18], as C3 plants share the same photosynthesis theory at the leaf level, i.e., Farquhar's leaf-level biochemical model [60], and BEPS has a "two-leaf" approach to upscale the ecosystem GPP to canopy level for various ecosystems including crops [49,61].…”
Section: Ecosystem Model For Gpp Simulationmentioning
confidence: 99%
“…The simulation of China's GPP by BEPS is subject to several sources of uncertainty inherent in the model's structure, parameterizations, processes, and input data (Chen et al, 2012;Chen et al, 2017;He et al, 2021a;Liu et al, 2018;Wang et al, 2021a). Leaf Area Index (LAI), a crucial input for the BEPS model, is derived from global remote sensing data that inherently possess uncertainties in spatial distribution and trend changes.…”
Section: Uncertainties In Beps Simulationsmentioning
confidence: 99%